Green low-carbon high-rutting-resistance asphalt concrete and preparation method thereof

By using high-density oxidized polyolefins and reactive polyurethane in asphalt concrete, combined with polyester modifiers and silane coupling agents, the problems of insufficient rut resistance and environmental pollution of existing asphalt concrete are solved, and efficient rut resistance improvement and environmentally friendly asphalt concrete materials are achieved.

CN119638274AActive Publication Date: 2025-03-18QINGDAO CHENGJIAN GRP SHIZHENG MATERIAL CO LTD +1

Patent Information

Application Number
CN202510075318.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing asphalt concrete has insufficient rut resistance under high temperature and heavy load conditions, and the selection and use of modifiers have problems such as environmental pollution and unstable performance, making it difficult to meet the long-term and durable needs of roads.

Method used

The synergistic effect of high-density oxidized polyolefin and reactive polyurethane is adopted, combining polyester modifiers and silane coupling agents to improve the performance of RAP and improve the rut resistance of asphalt concrete and reduce environmental pollution.

Benefits of technology

It significantly improves the high temperature stability and long-term durability of RAP, improves the rut resistance of asphalt concrete, reduces VOC emissions, conforms to the green and environmentally friendly design concept, and extends the service life of the road.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638274A_ABST
    Figure CN119638274A_ABST
Patent Text Reader

Abstract

The invention discloses green low-carbon high-rutting-resistance asphalt concrete and a preparation method thereof, and relates to the technical field of asphalt concrete. The technical scheme is as follows: RAP accounts for 30-40% of the mass of a new aggregate, 53-65 parts of the new aggregate, 3.2-4.1 parts of new asphalt, 4-6 parts of mineral powder, 0.3-0.4 part of high-density oxidized polyolefin, 0.05-0.1 part of a drying agent, 0.05-0.1 part of a lead salt stabilizer, 0.05-0.1 part of an auxiliary agent, 1.5-3 parts of reactive polyurethane, 3-6 parts of a polyester modifier, 0.5-2 parts of a silane coupling agent, 0.1-0.5 part of an antioxidant and 0.5-2 parts of a dispersing agent. Through the synergistic effect of high-density oxidized polyolefin and reactive polyurethane, the performance of aged asphalt in RAP is improved, the rutting resistance of asphalt concrete is improved, VOC emission is reduced, the sustainability of the material is enhanced, the long-term durability is improved, and the service life of a road is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asphalt concrete, and in particular to a green, low-carbon, high-rutting resistance asphalt concrete and a preparation method thereof. Background Art

[0002] With the rapid development of the global economy and the acceleration of urbanization, especially the frequent passage of heavy vehicles, the road traffic load has increased significantly. Road pavements are facing higher performance requirements, especially in high temperature environments and heavy traffic conditions. Traditional asphalt concrete pavements often experience rutting, which not only affects the service life of the road, but also increases maintenance costs. In order to improve the performance and rutting resistance of asphalt concrete, researchers and engineering technicians generally use asphalt modification technology. Modified asphalt can significantly improve the physical properties of asphalt by adding different types of functional modifiers, thereby improving the rutting resistance, aging resistance and high temperature stability of asphalt concrete. At present, commonly used asphalt modification methods include the use of modifiers such as polymers, rubber powder, and minerals, aiming to solve the performance deficiencies of traditional asphalt. However, these modification methods usually have certain technical challenges, including the selection of modifiers, dosage control, and stability of the modification effect.

[0003] In the prior art, a number of technologies have been proposed for improving the anti-rutting performance of asphalt concrete. Taking the patent with publication number CN 102910681A as an example, the patent uses aluminum chloride hexahydrate, waste rubber powder and drinking water to prepare an anti-rutting agent, which significantly improves the high-temperature anti-rutting ability of asphalt concrete. However, the use of waste rubber powder is large and it is easy to produce volatile organic compounds (VOCs), which not only increases the risk of environmental pollution, but also has an adverse effect on the long-term performance of asphalt concrete. Similarly, the patent with publication number CN 102887666A prepares an anti-rutting agent by using trivalent iron salts, synthetic rubber and sulfur stabilizers, which can improve the anti-rutting ability of asphalt concrete at a small addition amount, but its technical solution lacks consideration of environmental protection and sustainability, and in practical applications, the effectiveness and stability of the anti-rutting agent are still facing challenges. In addition, most of the existing anti-rutting modification technologies focus on improving the high-temperature resistance of asphalt, but often ignore the complexity of the material system and the long-term environmental impact.

[0004] At the same time, with the improvement of environmental awareness and the increasing shortage of resources, the recycling of recycled asphalt pavement (RAP) has become an important research direction for sustainable development. As an important recycled material, RAP has significant economic and environmental advantages. Its wide application can reduce dependence on natural resources and reduce waste emissions. However, RAP also faces many technical challenges in the process of reuse. Since RAP contains a large amount of aged asphalt and mineral materials, the physical and chemical properties of these components have changed, which limits the application of RAP in high-performance road construction. Especially when mixed with new asphalt, RAP may have problems such as reduced viscosity, severe aging, and unstable road performance, which limits its effectiveness as a high-performance road material. In addition, in the application of warm-mix asphalt, although it helps to reduce the mixing temperature and reduce the aging of asphalt, it still has disadvantages such as unstable material performance and short service life. Especially under high temperature and high load conditions, the anti-rutting performance of asphalt mixtures is still difficult to meet the needs of long-term durability of roads.

[0005] In the current technology, although some progress has been made in improving the anti-rutting performance of asphalt concrete by adding modifiers, there are a series of problems such as complex material system, improper selection of modifiers, and poor environmental friendliness. First of all, traditional modified asphalt mixtures usually rely on the combined use of multiple functional modifiers, especially the VOC emission problem with high environmental requirements has not been effectively solved. For example, the use of waste rubber powder and other organic modifiers will not only increase environmental pollution, but may also have a negative impact on the stability and long-term performance of asphalt mixtures. Secondly, although the existing anti-rutting modifiers have a certain effect in improving the high-temperature anti-rutting performance of asphalt, they have not been fundamentally improved in the performance of asphalt after aging. Under long-term use, the effect of the modifier may gradually weaken, and even the phenomenon of asphalt performance rebound may occur. In addition, in the application of recycled asphalt, the performance and road use effect of RAP are limited by the aging degree of its raw materials and the compatibility with new materials, resulting in unstable performance of RAP materials, and when added in large proportions, the high-temperature anti-rutting performance cannot be effectively guaranteed.

[0006] Especially when it comes to adding a large proportion of RAP, existing technologies often require a more complex material system to solve these problems. A wide variety of modifiers and regeneration agents are used, which increases the complexity and cost of the production process. In this process, how to balance the environmental protection, economy and high performance requirements of the materials is still a difficult problem to be solved. More importantly, most of the current technical solutions rely on warm mix asphalt or other low-temperature construction technologies. Although they effectively reduce the aging rate of asphalt at high temperatures, the combined effects of these technical solutions are still not enough to fully meet the high requirements for anti-rutting, anti-aging and service life in road construction.

[0007] In view of the defects of existing technologies, the current problem that needs to be solved urgently is how to simplify the modification system, reduce environmental pollution, and improve the sustainability and long-term performance of materials while ensuring high performance and anti-rutting performance. In particular, in the process of using recycled asphalt (RAP), how to effectively improve the performance of RAP and solve its aging, low viscosity and instability problems to improve the long-term durability and anti-rutting ability of roads. In addition, it is necessary to find an innovative solution that can simplify the traditional complex material system, while improving the comprehensive performance of asphalt concrete, reducing negative impacts on the environment, and adapting to the use requirements under heavy loads and high temperature environments. Summary of the invention

[0008] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a green, low-carbon and highly rutting-resistant asphalt concrete, which is composed of the following components in mass fractions: RAP accounts for 30-40% of the mass of new aggregate, 53-65 parts of new aggregate, 3.2-4.1 parts of new asphalt, 4-6 parts of mineral powder, 0.3-0.4 parts of high-density oxidized polyolefin, 0.05-0.1 parts of desiccant, 0.05-0.1 parts of lead salt stabilizer, 0.05-0.1 parts of additive, 1.5-3 parts of reactive polyurethane, 3-6 parts of polyester modifier, 0.5-2 parts of silane coupling agent, 0.1-0.5 parts of antioxidant and 0.5-2 parts of dispersant.

[0009] Preferably, the RAP comprises old asphalt and old aggregate in a mass ratio of 2:8-4:6, the old asphalt comprises one or more of base asphalt, SBS modified asphalt, and waste rubber powder modified asphalt; the old aggregate comprises one or more of basalt crushed stone, broken glass, and limestone crushed stone, and the RAP is screened into four particle sizes of 1-3mm, 3-5mm, 5-10mm, and 10-16mm.

[0010] Preferably, the new aggregate refers to one of basalt, limestone or diabase with four particle sizes of 1-3mm, 3-5mm, 5-10mm and 10-16mm.

[0011] Preferably, the new asphalt is one or more of 70# base asphalt, 90# base asphalt or SBS modified asphalt.

[0012] Preferably, the high-density oxidized polyolefin is one or both of high-density oxidized polyethylene and oxidized polypropylene, with a density of 0.98-1.02 g / cm3, a viscosity of 4100-4800 cp at 150°C, a melting point of 130°C-140°C, and a molecular weight of 2000-10000 g / mol.

[0013] Preferably, the polyester modifier is one of epoxy resin and maleic anhydride modified polyester; the silane coupling agent is one of aminosilane and vinyl silane.

[0014] Preferably, the mineral powder is limestone mineral powder, and the desiccant is one or more of silica gel, white carbon black or montmorillonite.

[0015] Preferably, the lead salt stabilizer is one or more of tribasic lead sulfate, dibasic lead phosphite or dibasic lead stearate; the auxiliary agent is one or more of phthalates and epoxidized soybean oil.

[0016] Preferably, the antioxidant is antioxidant 1024, and the dispersant is one of polyvinyl alcohol and sodium polyacrylate.

[0017] The present invention also provides a method for preparing the green, low-carbon, high-rutting-resistance asphalt concrete according to the above, the steps are as follows:

[0018] S1 RAP and new aggregate are placed in a high-energy ball mill for physical processing respectively. The ball milling time is 10-15 minutes to produce a microscopic rough structure on the aggregate surface. Then the silane coupling agent is dissolved in ethanol to form a solution with a mass concentration of 1-5%, and the solution is evenly coated on the surface of RAP and new aggregate. The solution is reacted for 1-2 hours to obtain pretreated RAP and new aggregate.

[0019] S2, in an environment of 100°C-110°C, mix the reactive polyurethane and epoxy resin and heat them to a molten state, and react for 30 minutes. After the reaction is completed, add the high-density oxidized polyolefin, continue heating and stirring for 10-15 minutes to ensure that it is evenly dispersed in the system to form a modifier;

[0020] S3: Add the additive, lead salt stabilizer and mineral powder to the premix, continue to heat to 130℃-140℃, fully mix with the new asphalt, then add the antioxidant and dispersant, and stir evenly for 15 minutes, mix completely, and obtain the pretreated asphalt mixture;

[0021] S4 performs gradation design on the pretreated RAP and new aggregate, and then heats them to 130℃-135℃ respectively and mixes them, then adds the modifier for dry mixing, and the dry mixing time is 2 minutes to ensure that the modifier is evenly coated on the aggregate surface, and then adds the pretreated asphalt mixture at a temperature of 160℃-170℃ for wet mixing for 3 minutes to ensure that the asphalt fully penetrates into the aggregate to form a uniform mixture. The gradation type of the gradation design is any one of AC, SMA, and OGFC.

[0022] S5 compacts the mixture when the temperature reaches 160°C-170°C.

[0023] The technical solution provided by the present invention brings beneficial effects:

[0024] Improve the performance of RAP: The synergistic effect of high-density oxidized polyolefin and reactive polyurethane can effectively improve the low viscosity and instability of aged asphalt in RAP. High-density oxidized polyolefin has good meltability and dispersibility, and can form a uniform film layer at a low temperature, enhancing the anti-rutting performance of the asphalt mixture. Reactive polyurethane reacts with the components in asphalt to improve its physical and chemical properties, increase the adhesion and high temperature resistance of asphalt. Therefore, the modified RAP has better high-temperature stability and long-term durability, solving the problems of aging, low viscosity and unstable performance in the reuse process of traditional RAP.

[0025] Improve the anti-rutting performance of asphalt concrete: The synergistic effect of polyester modifiers and high-density oxidized polyolefins makes asphalt concrete show excellent anti-rutting performance at high temperatures. Polyester modifiers can enhance the high-temperature bonding performance of asphalt through chemical cross-linking. High-density oxidized polyolefins can not only enhance the adhesion of asphalt, but also form a more stable dispersed structure in the asphalt mixture, thereby significantly improving the high-temperature anti-rutting ability of the mixture.

[0026] Reduce environmental pollution and improve material sustainability: The rational use of silane coupling agents and polyester modifiers not only improves the adhesion between asphalt and aggregate, but also reduces the emission of volatile organic compounds (VOCs). Silane coupling agents enhance the interfacial bonding between aggregate and asphalt by forming a chemical bonding layer on the surface of aggregate, avoiding the use of traditional organic solvents, thereby reducing the negative impact on the environment. At the same time, through the optimized modification system, the use of complex additives in traditional asphalt concrete is reduced, making the material system more simplified and in line with the design concept of green environmental protection.

[0027] Improve long-term performance and durability: The combination of reactive polyurethane and silane coupling agent strengthens the molecular cross-linking structure of the material, making asphalt concrete more resistant to aging, wear and water damage during long-term use. Especially under high temperature and heavy traffic conditions, the modified asphalt concrete can effectively maintain its original performance under the influence of rutting, crack expansion and other destructive factors, thus extending the service life of the road. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a photo of the pavement material interface of Example 1 of the present invention;

[0029] Figure 2 This is a photo of the rutting specimen of Example 1 of the present invention;

[0030] Figure 3This is a photo of the pavement core sample in Embodiment 1 of the present invention. Detailed implementation mode

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clear and understandable, the present invention will be further described in detail below in conjunction with embodiments. Of course, the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] Embodiment 1

[0033] S1. Pretreat RAP and new aggregates:

[0034] RAP accounting for 40% of the new aggregates (the mass ratio of old asphalt to old aggregates is 35:65, where the old asphalt is matrix asphalt mixture and the old aggregates are basalt gravels) and 58 parts of new aggregates (basalt gravels with particle sizes of 1-3 mm, 3-5 mm, 5-10 mm, and 10-16 mm) are respectively put into a high-energy ball mill for physical processing. The ball milling time is 12 minutes to produce a microscopic rough structure on the surface of the aggregates and increase the adhesion between the aggregates and the asphalt;

[0035] The silane coupling agent (vinyl silane) is dissolved in ethanol to form a solution with a mass concentration of 3%, and is evenly coated on the surfaces of RAP and new aggregates. The reaction time is 1.5 hours to form a stable surface chemical bonding layer.

[0036] S2. Preparation of the modifier:

[0037] At a temperature of 100°C - 110°C, 2 parts of reactive polyurethane and 4.5 parts of epoxy resin are mixed and heated to a molten state. Keep the temperature stable and react for 30 minutes to ensure complete reaction.

[0038] Add 0.35 parts of high-density oxidized polyolefin, continue heating and stirring for 10 minutes to ensure that the high-density oxidized polyolefin is evenly dispersed in the reaction system to form a uniform modifier.

[0039] S3. Pretreat the asphalt mixture:

[0040] Add 0.1 part of phthalate, 0.08 part of desiccant (selecting silica white), 0.08 part of lead salt stabilizer (tribasic lead sulfate) and 5% of mineral powder (limestone powder) to the premix, and continue heating to 130°C to 140°C.

[0041] Fully mix with 3.5% of new asphalt (70# matrix asphalt), then add 0.3 part of antioxidant (antioxidant 1024) and 1 part of dispersant (polyvinyl alcohol), and stir evenly. The stirring time is 15 minutes to ensure complete mixing, and a uniform pretreated asphalt mixture is obtained.

[0042] S4. Mixed asphalt concrete:

[0043] The pretreated RAP and new aggregate were graded to AC-13 and heated to 130°C to 135°C before mixing.

[0044] Add 2 parts of modifier and dry mix for 2 minutes to ensure that the modifier is evenly coated on the aggregate surface.

[0045] Then, the pretreated asphalt mixture is added, the temperature is controlled at 160℃ to 170℃, and wet mixing is carried out for 3 minutes to ensure that the asphalt fully penetrates into the aggregate to form a uniform mixture.

[0046] S5. Compacting and molding:

[0047] When the temperature of the mixture reaches 160°C to 170°C, the mixture is sent to the compacting equipment for compaction treatment to ensure the high anti-rutting performance and long-term durability of the asphalt concrete.

[0048] Example 2

[0049] The preparation was carried out in the same manner as in Example 1, except that RAP accounted for 35% of the new aggregate.

[0050] Example 3

[0051] The preparation was carried out in the same manner as in Example 1, except that RAP accounted for 30% of the new aggregate.

[0052] Example 4

[0053] The same preparation method as in Example 1 was used, except that 0.3 parts of high-density oxidized polyolefin, 3 parts of reactive polyurethane, 6 parts of polyester modifier, 2 parts of silane coupling agent,

[0054] Example 5

[0055] The same preparation method as in Example 1 was used, except that 0.4 parts of high-density oxidized polyolefin, 1.5 parts of reactive polyurethane, 6 parts of polyester modifier, 2 parts of silane coupling agent,

[0056] Example 6

[0057] The same preparation method as in Example 1 was used, except that 0.4 parts of high-density oxidized polyolefin, 1.5 parts of reactive polyurethane, 3 parts of polyester modifier, 0.5 parts of silane coupling agent,

[0058] Example 7

[0059] The same preparation method as in Example 1 was used, except that 0.3 parts of high-density oxidized polyolefin, 3 parts of reactive polyurethane, 3 parts of polyester modifier, 0.5 parts of silane coupling agent,

[0060] Example 8

[0061] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of the old asphalt to the old aggregate was 2:8.

[0062] Example 9

[0063] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of the old asphalt to the old aggregate was 4:6.

[0064] Example 10

[0065] The method is the same as that in Example 1, except that the old asphalt is SBS modified asphalt and the old aggregate is limestone gravel.

[0066] Embodiment 11

[0067] The preparation method is the same as that of Example 1, except that the high-density oxidized polyolefin is oxidized polypropylene, the silane coupling agent is aminosilane, the desiccant is montmorillonite, the lead salt stabilizer is dibasic lead phosphite, and the auxiliary agent is epoxidized soybean oil.

[0068] Comparative Example 1

[0069] S1. Pre-treatment of RAP and new aggregate:

[0070] RAP (the mass ratio of old asphalt to old aggregate is 35:65, where old asphalt is mixed with matrix asphalt and old aggregate is basalt crushed stone) accounting for 40% of new aggregate and 58 parts of new aggregate (basalt crushed stone with particle size of 1-3mm, 3-5mm, 5-10mm, 10-16mm) are placed in a high-energy ball mill for physical processing. The ball milling time is 12 minutes to produce a microscopic rough structure on the aggregate surface and increase the adhesion between the aggregate and asphalt;

[0071] S3. Pre-treatment of asphalt mixture:

[0072] Add 0.1 parts of phthalate, 0.08 parts of desiccant (white carbon), 0.08 parts of lead salt stabilizer (tribasic lead sulfate) and 5% of mineral powder (limestone mineral powder) to the premix, and continue heating to 130°C to 140°C.

[0073] Mix thoroughly with 3.5% new asphalt (70# base asphalt), then add 0.3 parts of antioxidant (antioxidant 1024) and 1 part of dispersant (polyvinyl alcohol), and stir evenly for 15 minutes to ensure complete mixing to obtain a uniform pretreated asphalt mixture.

[0074] S4. Mixed asphalt concrete:

[0075] The pretreated RAP and new aggregate were graded to AC-13, heated to 130°C to 135°C respectively, and then mixed and dry-mixed for 2 minutes.

[0076] Then, the pretreated asphalt mixture is added, the temperature is controlled at 160℃ to 170℃, and wet mixing is carried out for 3 minutes to ensure that the asphalt fully penetrates into the aggregate to form a uniform mixture.

[0077] S5. Compacting and molding:

[0078] When the temperature of the mixture reaches 160°C to 170°C, the mixture is sent to the compacting equipment for compaction treatment to ensure the high anti-rutting performance and long-term durability of the asphalt concrete.

[0079] Comparative Example 2

[0080] The preparation was carried out in the same manner as in Example 1, except that no reactive polyurethane was added.

[0081] Comparative Example 3

[0082] The preparation was carried out in the same manner as in Example 1, except that no polyester modifier or silane coupling agent was added.

[0083] Blank control example

[0084] Weigh 90.0% of new aggregate limestone and preheat it to 160℃. After drying, pour it into a mixing pot and mix it for 90s. The mixing temperature is 160℃. Heat 5.0% of 70# asphalt to 155℃ and add it into a mixing pot and mix it for 90s. Then add 5.0% of mineral powder and mix it for 90s to obtain hot mix asphalt concrete. Then, mold it at 140℃ to obtain the test piece.

[0085] Table 1 RAP and basalt synthesis grading scheme

[0086]

[0087]

[0088] Note: The gradation meets the gradation requirements of the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004). The Marshall forming and Marshall design methods are implemented in accordance with the provisions of the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004).

[0089] Experimental test:

[0090] The road performance of the examples, comparative examples and blank control group was tested according to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011).

[0091] Table 2 Road performance of the embodiments, comparative examples and blank control group

[0092]

[0093]

[0094] 1. Road performance

[0095] Dynamic stability: The dynamic stability of all examples is significantly better than that of the control group and the blank control group. This shows that after adopting the modifier system of the present invention, the asphalt concrete exhibits stronger anti-rutting performance, can effectively cope with the stress under high temperature and traffic load, and reduce the formation of rutting.

[0096] Residual stability: The residual stability in the examples is generally higher than that in the control group, which shows the superiority of the modified material in improving the long-term stability and durability of asphalt concrete. The modified asphalt concrete can better maintain its physical properties during use and extend the service life of the material.

[0097] Freeze-thaw splitting strength ratio: The embodiments of the present invention perform excellently in the freeze-thaw splitting strength ratio, which is significantly higher than that of the control group. Especially in harsh environments, the modified materials show stronger anti-freeze-thaw performance, reduce the crack expansion caused by freeze-thaw action, and improve the durability of asphalt concrete.

[0098] Flexural strain: The flexural strain of the examples is generally higher, indicating that the modified asphalt concrete has better toughness and crack resistance. Higher flexural strain values ​​indicate that the modified asphalt concrete can undergo greater deformation without breaking when subjected to external forces, improving its performance under high temperature and heavy load conditions.

[0099] 2. VOC emissions

[0100] VOC emissions: The VOC emissions of the embodiment are significantly lower than those of the control group, especially after the use of silane coupling agents and other green additives, which can effectively reduce the emission of volatile organic compounds. In contrast, the VOC emissions of the control group and the blank control group are higher, indicating that the modified system of the present invention can effectively reduce environmental pollution and meet the design requirements of green environmental protection.

[0101] 3. Comparative Analysis

[0102] Compared with the control group and the blank control group, the embodiments of the present invention show obvious advantages in multiple important performance indicators such as dynamic stability, residual stability, freeze-thaw splitting strength ratio and bending-tension strain, especially in terms of rutting resistance, durability and environmental performance. In particular, in the embodiments, the performance of asphalt concrete is significantly improved through reasonable material combination and modification technology.

[0103] 4. Summary of beneficial effects

[0104] According to the combination of experimental data and technical solutions, the following are the beneficial effects of the present invention:

[0105] Improve the performance of RAP: The present invention significantly improves the low viscosity and instability of aged asphalt in RAP by using the synergistic effect of high-density oxidized polyolefin and reactive polyurethane, and enhances its high temperature stability and long-term durability. The modified RAP can be better integrated into the asphalt concrete system, improving the comprehensive performance of the material.

[0106] Improve the anti-rutting performance of asphalt concrete: Through the synergistic effect of polyester modifiers and high-density oxidized polyolefins, asphalt concrete exhibits excellent anti-rutting performance under high temperature conditions. This shows that the present invention can effectively improve the high-temperature stability of asphalt concrete and extend the service life of the road.

[0107] Reduce environmental pollution and improve material sustainability: The rational application of silane coupling agents and polyester modifiers not only improves the adhesion between asphalt and aggregate, but also effectively reduces VOC emissions and the negative impact of volatile organic compounds on the environment, which is in line with the green and environmentally friendly design concept.

[0108] Improve long-term performance and durability: The modification technology of the present invention improves the anti-aging, anti-wear and anti-water damage capabilities of asphalt concrete by strengthening the cross-linking structure between molecules. Under high temperature, heavy traffic and adverse weather conditions, the modified asphalt concrete can effectively maintain its excellent performance and extend the service life of the road.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A green, low-carbon, high-rutting resistance asphalt concrete, characterized in that: The asphalt concrete is composed of the following components in mass fractions: RAP accounting for 30-40% of the mass of new aggregate, 53-65 parts of new aggregate, 3.2-4.1 parts of new asphalt, 4-6 parts of mineral powder, 0.3-0.4 parts of high-density oxidized polyolefin, 0.05-0.1 parts of desiccant, 0.05-0.1 parts of lead salt stabilizer, 0.05-0.1 parts of additives, 1.5-3 parts of reactive polyurethane, 3-6 parts of polyester modifier, 0.5-2 parts of silane coupling agent, 0.1-0.5 parts of antioxidant, and 0.5-2 parts of dispersant.

2. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The RAP comprises old asphalt and old aggregate in a mass ratio of 2:8-4:

6. The old asphalt comprises one or more of base asphalt, SBS modified asphalt, and waste rubber powder modified asphalt; the old aggregate comprises one or more of basalt crushed stone, broken glass, and limestone crushed stone. The RAP is screened into four particle sizes of 1-3mm, 3-5mm, 5-10mm, and 10-16mm.

3. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The new aggregate refers to one of basalt, limestone or diabase with four particle sizes of 1-3mm, 3-5mm, 5-10mm and 10-16mm.

4. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The new asphalt is one or more of 70# base asphalt, 90# base asphalt or SBS modified asphalt.

5. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The high-density oxidized polyolefin is one or both of high-density oxidized polyethylene and oxidized polypropylene, and its density is 0.98-1.02 g / cm 3 , the viscosity at 150℃ is 4100-4800cp, the melting point is 130℃-140℃, and the molecular weight is 2000-10000g / mol.

6. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The polyester modifier is one of epoxy resin and maleic anhydride modified polyester; the silane coupling agent is one of aminosilane and vinyl silane.

7. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The mineral powder is limestone mineral powder, and the desiccant is one or more of silica gel, white carbon black or montmorillonite.

8. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The lead salt stabilizer is one or more of tribasic lead sulfate, dibasic lead phosphite or dibasic lead stearate; the auxiliary agent is one or more of phthalate ester and epoxidized soybean oil.

9. The green, low-carbon, high-rutting-resistance asphalt concrete according to claim 1, characterized in that: The antioxidant is antioxidant 1024, and the dispersant is one of polyvinyl alcohol and sodium polyacrylate.

10. A method for preparing a green, low-carbon, high-rutting-resistance asphalt concrete according to any one of claims 1 to 9, characterized in that: Here are the steps: S1 RAP and new aggregate are placed in a high-energy ball mill for physical processing to produce a microscopic rough structure on the surface of the aggregate, and then the silane coupling agent is dissolved in ethanol to form a solution with a mass concentration of 1-5%, and the solution is evenly coated on the surface of RAP and new aggregate, and reacted for 1-2 hours to obtain pretreated RAP and new aggregate; S2, in an environment of 100°C-110°C, mix the reactive polyurethane and epoxy resin and heat them to a molten state, and react for 30 minutes. After the reaction is completed, add the high-density oxidized polyolefin, continue heating and stirring for 10-15 minutes to ensure that it is evenly dispersed in the system to form a modifier; S3: Adding additives, lead salt stabilizers and mineral powder to the premix, continuing to heat to 130°C-140°C, fully mixing with new asphalt, then adding antioxidants and dispersants, stirring and mixing evenly to obtain a pretreated asphalt mixture; S4 performs gradation design on the pretreated RAP and new aggregate, and then heats them to 130℃-135℃ respectively and mixes them, then adds the modifier for dry mixing to ensure that the modifier is evenly coated on the aggregate surface, and then adds the pretreated asphalt mixture at a temperature of 160℃-170℃ for wet mixing to ensure that the asphalt fully penetrates into the aggregate to form a uniform mixture. The gradation type of the gradation design is any one of AC, SMA, and OGFC. S5 compacts the mixture when its temperature reaches 160°C-170°C.

Citation Information

Patent Citations

  • Asphalt mixture with high anti-rutting capacity and preparation method thereof

    CN102887666A

  • Preparation method of Mn3O4 nano particles

    CN102910681A

  • Anti-rutting asphalt modifier, preparation method thereof, modified asphalt and application thereof

    CN101906224A

  • Anti-rut agent composition for high-performance composite polyolefin asphalt mixture and preparation method thereof

    CN104629150A

  • Recycled asphalt concrete and preparation method thereof

    CN109704648A

Cited By

  • High-durability asphalt concrete reservoir basin impermeable material and application method thereof

    CN120271275A

  • A high-durability asphalt concrete reservoir waterproofing material and its application method

    CN120271275B